Internal anatomy of the terminal ampoule of Metapenaeus monoceros (Fabricius, 1798) and its role in spermatophore formation - Abraham, Joice; Manisseri, Mary K; N.K, Sanil (Indian Journal of Fisheries, 2012)
Internal anatomy of terminal ampoule of Metapenaeus monoceros and the role played by this organ in spermatophore formation were elucidated employing histological and ultrastructural techniques. Terminal ampoule of mature male specimens consisted of an outer layer of connective tissue surrounding a layer of circular and longitudinal muscle fibres. The lumen of terminal ampoule was divided into four chambers lined by basophilic glandular epithelial cells, which showed intense secretary activity. One of the chambers had sperm mass surrounded by primary and secondary spermatophore layers. Formation of an eosinophilic matrix and adhesive globules resulting from secretions by glandular epithelial cells were observed in other chambers. Ultrastructural studies revealed that the cytoplasm of the epithelial cells had numerous free ribosomes, concentric arrangement of rough endoplasmic reticulum with vesicles often discharged into the lumen, and numerous electron dense bodies, all confirming the intense secretary activity taking place in the ampoule.